Pendekatan Filosofis dalam Hukum Islam: Kajian atas Pengertian, Urgensi, dan Sejarah Filsafat Hukum Islam.: Philosophical Approach in Islamic Law: Study of the Definition, Urgency, and History of Islamic Legal Philosophy - Muh. Isra Syarif; Lomba Sultan; Ahmad Musyahid (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This paper examines the definition, urgency, and historical growth and development of Islamic legal philosophy as a philosophical approach to Islamic law. Islamic legal philosophy is defined as a discipline that critically understands rules derived from the Qur'an and Hadith to address various human life issues, by exploring the deeper meaning of why a law is established, its objectives, and how it reflects values of justice, mercy, and public welfare in society. The purpose of this study is to thoroughly examine the definition, urgency, and historical growth and development of Islamic legal philosophy as an integral approach to understanding and developing Islamic law contextually, rationally, and humanistically. The methodology employed in this paper is a literature review, analyzing various scholarly works and the thoughts of Muslim scholars and philosophers on Islamic legal philosophy from classical to contemporary periods. The results indicate that Islamic legal philosophy holds high urgency in the development of Islamic legal studies, both in academic and social practical contexts, due to its ability to address challenges of legal contextualization, strengthen the objectives and values of Islamic law, expand ijtihad methodology, respond to modern criticisms, uncover the secrets of Sharia, analytically understand legal causes ('illat), and distinguish between static and dynamic elements in law. This research contributes to the discipline of Islamic law by providing a complete, in-depth, and perpetually relevant understanding (sholih kulli zaman wa al-makan) , and by serving as a bridge between normative texts and the dynamic realities of society.